(1-tanA)^2 + (1-cotA)^2 = (secA-cosecA)^2
Answers
Answered by
38
Hope it will help you!
Attachments:
![](https://hi-static.z-dn.net/files/d61/ad86e899622b41ed76883fbc1d1b1875.jpg)
arya4811:
Thanku very much brother
Answered by
5
sec²A+cosec²A-(2tanA+2cotA)=sec²A+cosec²A -(2 x secA x cosecA)
2(tanA+cotA)=2xsecAxcosecA
tanA+cotA=secA x cosecA
2(tanA+cotA)=2xsecAxcosecA
tanA+cotA=secA x cosecA
Similar questions
English,
8 months ago
Biology,
1 year ago
Math,
1 year ago
History,
1 year ago
Computer Science,
1 year ago